2014
DOI: 10.1590/s0103-84782014000600004
|View full text |Cite
|
Sign up to set email alerts
|

Influência do espaçamento e da população de plantas de sorgo sacarino em diferentes épocas semeadura

Abstract: Infl uência do espaçamento e da população de plantas de sorgo sacarino em diferentes épocas semeadura.Ciência Rural, v.44, n.6, jun, 2014. 975Infl uência do espaçamento e da população de plantas de sorgo sacarino em diferentes épocas semeadura

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 4 publications
1
7
0
10
Order By: Relevance
“…Likewise, FERNANDES et al (2014) evaluated the effect of BRS 506 sweet sorghum plants arrangement in two crop years (normal and late seasons), when the spacing ranged from 0.5 to 0.8m between rows, and plant population ranged from 80,000 to 140,000 plants ha -1 , and found that the seeding in normal season resulted in higher yield of fresh weight of stems and fresh weight of total biomass per cultivated area, and 0.5m row spacing resulted in higher total biomass yield in the two crop years studied.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, FERNANDES et al (2014) evaluated the effect of BRS 506 sweet sorghum plants arrangement in two crop years (normal and late seasons), when the spacing ranged from 0.5 to 0.8m between rows, and plant population ranged from 80,000 to 140,000 plants ha -1 , and found that the seeding in normal season resulted in higher yield of fresh weight of stems and fresh weight of total biomass per cultivated area, and 0.5m row spacing resulted in higher total biomass yield in the two crop years studied.…”
Section: Resultsmentioning
confidence: 99%
“…According to Fernandes et al (2014), the reduction of row spacing for the sorghum crop results in agronomic gains of great importance for the ethanol production. On the other hand, in relation to plant population, the result does not always indicate an effect on the main production variables, due to the environmental variation and the different row spacings evaluated.…”
Section: Palavras-chavementioning
confidence: 99%
“…The average yield of irrigated treatments was 63.98 t ha -1 , a value within the productivity range reported by Pereira Filho et al (2013) for different sorghum cultivars, and higher than the average yield quoted by EMBRAPA (2012), of 50 t ha -1 . Fernandes et al (2014) obtained an average yield of 60.97 t ha -1 with the BRS 506 genotype in harvest condition.…”
Section: Resultsmentioning
confidence: 96%